PENGEMBANGAN POTENSI PERKEBUNAN SEBAGAI SEKTOR UNGGULAN DESA MATARU UTARA - Tabita Plaikari; Yesgelode Lauata; Petrus Mau Tellu Dony (JOURNAL OF COMMUNITY DEDICATION, 2026)
This study aims to analyze the potential of the plantation sector as a leading sector in Mataru Utara Village, with a focus on candlenut, which serves as the community’s primary commodity. Using a qualitative method through interviews, observations, and documentation, the study describes the conditions of candlenut production, processing, and marketing in the village. The results indicate that candlenut is the main source of income and has considerable economic potential. This commodity can be developed not only as a raw product but also into various value-added processed products. However, its potential has not been fully optimized due to limited production facilities, low post-harvest skills, a lack of knowledge about appropriate technology, and restricted market access. To support the development of this sector, training on candlenut processing, strengthening farmer groups or farmer institutions, improving production infrastructure, and expanding market access are necessary. With these efforts, the candlenut plantation sector has the potential to become a leading sector that can improve the income and welfare of the community in Mataru Utara Village.